How does bile salt penetration affect the self-assembled architecture of pluronic P123 micelles? – light scattering and spectroscopic investigations1. Issue 30 (14th August 2015) - Roy, Arpita; Kundu, Niloy; Banik, Debasis; Kuchlyan, Jagannath; Sarkar, Nilmoni
<x xml:space="preserve">Abstract</x> The triblock copolymer of the type (PEO)20–(PPO)70–(PEO)20 (P123) forms a mixed supramolecular aggregate with different bile salts, sodium deoxycholate (NaDC) and sodium taurocholate (NaTC), having different hydrophobicity.